Effect of different shredded simili paper size on compressive strength of mortar - Syafiq Naqiuddin, Yusuf (2016)
Paper waste is the third largest pollutant consumer as it threatens the environment. In 2010, from 96.5 million tonnes of Europe production generates to 8.9 million tonnes of waste. At the same time, 49 million tonnes production of recycled paper produces 8.2 million tonnes of solid waste. Hence, utilisation of paper waste in mortar material is an approach in preserving the nature. This experimental work is conducted to investigate the compressive strength of mortar containing different shredded paper size as partial replacement for sand (fine aggregates), known as papercrete. Two types of specimens’ size, 100x100x100 mm was made using two different shredded paper sizes and control mix. The specimens were subjected to compressive strength and water absorption test. The type of shredded paper use is simili paper with the size of 3x25 mm (Mix 1) and 2x8 mm (Mix 2), collected from the Faculty of Civil Engineering & Earth Resources (FKASA) and Concrete Laboratory in UMP. Then, the specimens were subjected to two types of curing that is air curing and seal curing up to 120 days. The results show that the specimen prepared using smaller size of shredded paper exhibit better performance in terms of compressive strength and water absorption compared to the one produced with larger size of shredded paper.